Natural products reverse cancer multidrug resistance - Zou, Jia-Yu; Chen, Qi-Lei; Luo, Xiao-Ci; Damdinjav, Davaadagva; Abdelmohsen, Usama Ramadan; Li, Hong-Yan; Battulga, Tungalag; Chen, Hu-Biao; Wang, Yu-Qing; Zhang, Jian-Ye (Frontiers in Pharmacology, 2024)
Cancer stands as a prominent global cause of death. One of the key reasons why clinical tumor chemotherapy fails is multidrug resistance (MDR). In recent decades, accumulated studies have shown how Natural Product-Derived Compounds can reverse tumor MDR. Discovering novel potential modulators to reduce tumor MDR by Natural Product-Derived Compounds has become a popular research area across the globe. Numerous studies mainly focus on natural products including flavonoids, alkaloids, terpenoids, polyphenols and coumarins for their MDR modulatory activity. Natural products reverse MDR by regulating signaling pathways or the relevant expressed protein or gene. Here we perform a deep review of the previous achievements, recent advances in the development of natural products as a treatment for MDR. This review aims to provide some insights for the study of multidrug resistance of natural products.